PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP KETIDAKPUASAN KERJA KARYAWAN - Diterima Hasrat Niat Buulolo; Mukhamad Kholil Aswan (Media Bina Ilmiah, 2025)
This study aims to analyze the effect of work stress and workload on employee job dissatisfaction at PT TI Mutsuoka Winner Industry. The method used in this study is a quantitative method with a descriptive approach and multiple linear regression analysis. Data were collected through questionnaires and analyzed using t-test and F-test to determine the partial and simultaneous effects between variables. The results of the study indicate that partially, work stress has a positive and significant effect on job dissatisfaction with a significance value of 0.000 (<0.05) and a regression coefficient of 0.933. Workload also has a positive and significant effect on job dissatisfaction, with a significance value of 0.003 and a regression coefficient of 0.825. Simultaneously, both variables have a significant effect on job dissatisfaction, as evidenced by the results of the F test with a significance value of 0.000 and an R Square value of 0.626, which indicates that 62.6% of the variation in job dissatisfaction can be explained by work stress and workload. This study concludes that work stress is a dominant factor influencing employee job dissatisfaction. Therefore, companies need to implement effective stress management and workload management strategies to improve employee job satisfaction and maintain productivity